Hubungan Performa Fisik dengan Prognosis Pasien Gagal Jantung - Palilati, Nurfadhilah H.; Wantania, Frans E. N.; Rotty, Linda W. A. (Universitas Sam Ratulangi, 2021)
Abstract: Heart failure is a serious health problem and a leading cause of death, illness, and poor quality of life. Although the diagnosis and treatment of this disease has significant progress, the prognosis is still poor. The physical performance of patients with heart failure, for example, measured by a 6-minute walking test can be used to assess the functional capacity and assess the prognosis of the patient. This study was aimed to determine the relationship between physical performance and prognosis of patients with heart failure. This was a literature review study using literatures obtained from three databases, namely Pubmed, Science Direct, and Google Scholar. The keywords used in searching the literatures were